2003
DOI: 10.1160/th03-06-0363
|View full text |Cite
|
Sign up to set email alerts
|

High D-dimer levels predict cardiovascular events in patients with chronic atrial fibrillation during oral anticoagulant therapy

Abstract: Atrial fibrillation (AF) is associated with hemostatic abnormalities and increased risk of thrombotic cardiovascular events even during oral anticoagulant therapy (OAT). The aim of our study was to evaluate the predictive value of hemostatic markers for the risk of major cardiovascular events during OAT. The study group comprised 113 patients with chronic AF (70.2 +/- 5.4 years old, 60% men), referred for OAT. Established clinical risk factors and levels of prothrombin fragment 1+2 (F1+2), thrombin-antithrombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(34 citation statements)
references
References 26 publications
4
29
0
1
Order By: Relevance
“…19 Furthermore, D-dimer levels have been shown to predict thromboembolic events even in patients with anticoagulated AF. 20 Results of the current study document an elevation in the prothrombotic markers fibrinogen ( Figure 3A) and D-dimer ( Figure 3B). Fibrinogen elevation positively correlated with hs-CRP elevation.…”
Section: Inflammation and Thrombotic Risksupporting
confidence: 50%
“…19 Furthermore, D-dimer levels have been shown to predict thromboembolic events even in patients with anticoagulated AF. 20 Results of the current study document an elevation in the prothrombotic markers fibrinogen ( Figure 3A) and D-dimer ( Figure 3B). Fibrinogen elevation positively correlated with hs-CRP elevation.…”
Section: Inflammation and Thrombotic Risksupporting
confidence: 50%
“…[7][8][9]25 In the present study, we observed no significant association of D-dimer with risk of recurrent stroke. Two prospective studies 37,38 have reported significant associations of D-dimer with risk of stroke in patients with atrial fibrillation. Only 11% of patients with ischemic stroke had atrial fibrillation in this study (Table 1).…”
Section: Woodward Et Al Hemostatic Variables and Recurrent Stroke 2145mentioning
confidence: 99%
“…In a study by Vene and colleagues, high levels of peripheral vein D-dimer indicated an unfavorable prognosis in AF patients, even during oral anticoagulant therapy. 22 Elevated D-dimer (≥0.5 mg/ml) levels in peripheral veins have been associated with both thromboembolic (hazard ratio 15.8, P<0.01) and cardiovascular events (hazard ratio 7.64, P<0.01) in patients with AF during warfarin therapy. 8 Anticoagulation control quality affects the peripheral vein D-dimer levels.…”
Section: Yashiro Y Et Almentioning
confidence: 98%